Konseptualisasi mitigasi bencana melalui perspektif kebijakan publik - Burhanudin Mukhamad Faturahman (Universitas Merdeka Malang, 2018)
Disaster mitigation is the initial phase of disaster management more leads to disaster risk reduction for disaster-prone areas to reduce the larger impact caused by natural disasters. The purpose of this study discusses disaster mitigation policies in disaster-prone areas in terms of medium-term Regional development plan (RPJMD) in Pacitan Ponorogo and Trenggalek regency. The descriptive method was chosen to provide the description about mitigation of disaster-prone areas in the further theoretical and comparative analysis of secondary data document RPJMD. The results showed, disaster mitigation conceptually as output, disaster-prone areas of empirical conditions as input, process the Executive and the legislature as a process in the public policy cycle. In addition, disaster mitigation included in the agenda of the policy in the RPJMD, Pacitan Ponorogo and Trenggalek Regency through development programs of prevention and disaster preparedness to enhance the capacity of local governments in the face of natural disasters.